Два ювілеї академіка Валерія Смолія (до 75-ліття від дня народження та 30-річчя творчої і науково-організаційної діяльності як головного редактора "Українського історичного журналу") - Ясь, О.В. (Вісник НАН України, 2025)
1 січня 2025 р. виповнюється 75 років українському історику, фахівцю з історичної медієвістики та ранньої новістики, громадському та політичному діячеві, лауреату Державної премії України в галузі науки і техніки (2001), заслуженому діячу науки і техніки України (1998), директору Інституту історії України НАН України (з 1993), академіку-секретарю Відділення історії, філософії та права НАН України (з 2015), доктору історичних наук (1985), професору (1999), академіку НАН України (1995) Валерію Андрійовичу Смолію. Цей ювілей збігся в часі з 30-літтям його діяльності як головного редактора «Українського історичного журналу». У статті стисло висвітлено передісторію змагань українських істориків за науковий журнал у радянській Україні, його роль у формуванні інституціональної мережі української історичної науки післясталінської доби, виклики 1990-х років та метаморфозу часопису від періодичного видання республіканської, а згодом пострадянської науки до сучасної інституціональної платформи українських істориків. January 1, 2025, marks the 75th anniversary of the birth of a prominent Ukrainian historian, specialist in medieval and early modern history, initiator and organizer of numerous key projects of Ukrainian historical science in the 1990s and 2000s, public figure, vice prime minister of Ukraine for humanitarian policy (1997—1999), full knight of the Order of Prince Yaroslav the Wise and the Order of Merit, Laureate of the State Prize of Ukraine in Science and Technology (2001), Honored Worker of Science and Technology of Ukraine (1998), Director of the Institute of History of Ukraine of the National Academy of Sciences of Ukraine (since 1993), Doctor of Historical Sciences (1985), Professor (1999), Academician of the National Academy of Sciences of Ukraine (1995), Academician-Secretary of the Department of History, Philosophy and Law (since 2015) Valerii Smolii. Th is life anniversary coincides with the 30th anniversary of his creative, scientific, and organizational activity as the chief scientific editor of the “Ukrainian Historical Journal”. The article briefly highlights the background of the Ukrainian historians’ eff orts aimed at championing a scientific journal in Soviet Ukraine. The author emphasizes the exceptional role of the journal in the formation of the institutional network of Ukrainian historical science in the post-Stalin era. The horizon of challenges faced by the journal’s editor-in-chief in the 1990s has been outlined. The metamorphosis of the journal from a periodical of republican and later post-Soviet scholarship to a modern institutional platform for Ukrainian historians has been considered. The role of the editor-in-chief in shaping and changing the editorial policy of the journal in the 2000s has been highlighted, particularly in light of the demands and challenges of the current Russian-Ukrainian war.